(untitled) (Profesional de la información, 2016)
Born-digital media is influenced by many factors. This study compares the perceptions of digital and traditional (newspaper, radio, TV, news agencies, etc.) journalists and investigates their perception of threats to their professions. This paper shows data from a national survey (probabilistic, stratified by type of outlet and region) to 390 journalists in Spain between March 2014 and May 2015. Reporters were surveyed about their differing influences (political, economic, organizational, professional routines, and reference groups) in their jobs. Even where there are clear socio-demographic differences, data shows that, except for the influence of reference groups, all journalists hold similar perceptions. Theoretical and practical implications are discussed.